PEMAHAMAN SILA KETUHANAN YANG MAHA ESA MENURUT IMAN KRISTEN (Bagian 1) - Sumarno (Jurnal Arrabona, 2019)
The existence of various kinds of religions and beliefs in Indonesia, naturally leads to various kinds of understanding of the precepts of the Almighty God. This fact cannot be avoided, because each religion is based on the conception and teachings of its own religion. Moreover, each religion has its own sacred book. This often leads to serious debates between adherents of one religion with another and not even rarely cause disputes. This fact is also what often cornered and branded Christianity as a polytheistic religion. The question is, is it true that Christianity is a polytheistic religion? Is it true that God is three? Is it true that unity in Christianity makes no sense at all? Or is Christianity the opposite which is true monotheism? It is on this basis that the writer raises this point as an attempt to provide an explanation, description and answer to those who do not understand the conception of oneness according to the Bible.